Pengaruh Financial Distress, Audit Report Lag dan Audit Tenure terhadap Integritas Laporan Keuangan: Studi Empiris pada Perusahaan BUMN yang terdaftar di Bursa Efek Indonesia - Corry Anastasia Mahendra; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This research aims to find out the effect of financial distress, audit report lag and audit tenure on the integrity of financial statements in state owned companies listed on the Indonesia Stock Exchange in 2016-2020.This research is a quantitative research. The sample collected was 85 data based on purposive sampling technique. The data used is secondary data obtained from www.idx.co.id or company website and other sites related to this research. The research data was analyzed using multiple linear regression analysis. Based on statistical analysis, it can be concluded that financial distress and audit report lag has a negative effect on the integrity of financial statements. Audit tenure has no effect on the integrity of financial statements.